Core–shell bioprinting of vascularized in vitro liver sinusoid models. (27th September 2022) - Taymour, Rania; Chicaiza-Cabezas, Nathaly Alejandra; Gelinsky, Michael; Lode, Anja
Abstract: In vitro liver models allow the investigation of the cell behavior in disease conditions or in response to changes in the microenvironment. A major challenge in liver tissue engineering is to mimic the tissue-level complexity: besides the selection of suitable biomaterial(s) replacing the extracellular matrix (ECM) and cell sources, the three-dimensional (3D) microarchitecture defined by the fabrication method is a critical factor to achieve functional constructs. In this study, coaxial extrusion-based 3D bioprinting has been applied to develop a liver sinusoid-like model that consists of a core compartment containing pre-vascular structures and a shell compartment containing hepatocytes. The shell ink was composed of alginate and methylcellulose (algMC), dissolved in human fresh frozen plasma. The algMC blend conferred high printing fidelity and stability to the core–shell constructs and the plasma as biologically active component enhanced viability and supported cluster formation and biomarker expression of HepG2 embedded in the shell. For the core, a natural ECM-like ink based on angiogenesis-supporting collagen-fibrin (CF) matrices was developed; the addition of gelatin (G) enabled 3D printing in combination with the plasma-algMC shell ink. Human endothelial cells, laden in the CFG core ink together with human fibroblasts as supportive cells, formed a pre-vascular network in the core in the absence and presence of HepG2 in the shell. The cellular interactions occurring in the triple culture model enhanced the albumin secretion. In conclusion, core–shell bioprinting was shown to be a valuable tool to study cell–cell-interactions and to develop complex tissue-like models.